(untitled) (Jurnal Bina Praja, 2022)
This study focuses on the collaboration between the Ministry of Education, Culture, Research and Technology of the Government of Indonesia, the Bhakti Jaya Indonesia Foundation, and the Universitas Pembangunan Nasional "Veteran" Jawa Timur to improve the economic protection of Indonesian migrant workers in Taiwan. The three actors are representatives of state actors and non-state actors. The financial condition of Indonesian migrant workers is often in the spotlight with their inability to get out of the debt trap and consumptive financial management. Moreover, this condition finally seemed to throw away all the hard work of PMI while working abroad. Based on this fact, an institutional collaboration between state and non-state actors has initiated a financial literacy program for Indonesian migrant workers, which is indeed the implementation of the normative law of economic protection in accordance with the mandate of state law. This research was conducted using a qualitative descriptive approach which aims to describe the phenomena raised by the researchers through contextual studies. Researchers also use a literature review instrument to complement the research approach. Meanwhile, researchers used qualitative data analysis that took primary and secondary data for data analysis. This study highlights how the gaps in Indonesian migrant workers’ inability to manage their finances can be addressed with good collaboration between state and non-state actors. It is hoped that from this research, there will be many similar programs to improve Indonesian migrant workers’ welfare, especially in Taiwan.